EFEKTIVITAS PENGGUNAAN “BUKU SAKU CALON PENGANTIN SEHAT” DALAM PERSIAPAN PRAKONSEPI - Rezah Andriani; Ria Gustirini; Fadilah Zhafarina (JOMIS (Journal of Midwifery Science), 2026)
Reproductive health issues in Indonesia still require special attention because they have not been fully addressed. This is evident in the high rate of early marriage. According to data from the Religious Courts Agency, there were 50,673 dispensations for early marriage in Indonesia in 2022, a 17.54% decrease from the 61,449 cases in 2021. The high incidence of teenage pregnancy (16.19%) and the low level of adolescent knowledge about reproductive health remain. Reproductive health education provided to prospective brides is an effort to fulfill reproductive rights for women. The purpose of this study was to determine the effectiveness of using the "healthy prospective bride pocket book" in increasing knowledge about preconception preparation and the readiness of prospective brides to enter the gate of marriage. This study uses a quantitative approach, the method used in this study is the quasi-experimental method with a one group pretest-posttest design. This study was conducted at the 1 Ulu Palembang Health Center. The sample of this study was 45 prospective brides. The results of the study showed significant differences in pre and post intervention of providing the Healthy Prospective Bride pocket book to prospective brides (catin) for readiness to marry (z -5,847 dan significant p 0,000) and knowledge of prospective brides (z -5,863 dan significant p 0,000). So it can be concluded that providing the healthy prospective bride pocket book is effective in increasing readiness to marry and knowledge of prospective brides and can be recommended for use in various health center and KUA activities related to prospective brides